STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - Mardani Mardani; Herla Astuti (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
In the context of fostering religious character among students at SMPN 2 Tanah Grogot, a variety of strategies involving different methods are employed. These methods encompass habituation, exemplification, and discipline. Habituation involves consistent and routine activities such as congregational prayers, maintaining decorum, and using polite language. Teachers lead by example through their own virtuous behavior and encourage students to perform religious practices such as the Dhuha prayer. Discipline is enforced through established rules that students must adhere to, with consequences for rule violations. The outcomes of these strategies include the development of religious character in students, characterized by strong faith, adherence to religious principles, good moral conduct, exemplary behavior, honesty, and an awareness of the importance of cleanliness. Furthermore, students exhibit increased discipline and confidence in practicing their religious duties. These efforts are consistently implemented and receive support from the school, including the school's principal, in creating an environment conducive to the cultivation of religious character.